Graffiti sztuką dialogu i przejawem dezorganizacji przestrzennej - Nowak-Kluczyński, Konrad (Studia Edukacyjne, 2025)
The article addresses the phenomenon of graffiti as a multidimensional practice at the intersection of art, subculture, and social protest. The author presents graffiti as a form of visual communication and emotional-ideological expression, as well as a manifestation of spatial disorganization within the urban context. Particular attention is given to the relationship between graffiti and the hip-hop subculture, as well as its evolution toward a tool of symbolic contestation and a carrier of social dialogue. The study also explores the origins and functions of graffiti, including its historical and contemporary forms, with examples of graffiti found on the walls of Polish cities. The author attempts to characterize the graffiti artist as an urban actor—an artist, activist, or outsider—operating within informal, often illegal street art. This article contributes to broader discussions on youth subcultures, social communication, and urban art, offering an interpretation of graffiti as a form of dialogue with significant social and cultural potential.